Cassava response to the integrated use of manure and NPK fertilizer in Zambia - Gizachew Kebede Biratu; Eyasu Elias; Pheneas Ntawuruhunga; Gudeta W. Sileshi (Heliyon, 2018)
Cassava is Africa's second most important food source in terms of calories consumed per capita. However, farmers use little or no fertilizer on cassava and scant information is available regarding the cassava yield response to mineral and organic fertilizer inputs in Zambia. This study was undertaken to determine the response of cassava to the integrated use of organic and inorganic nutrient sources in two contrasting agroecological zones of Zambia; Mansa located in Zone III and Kabangwe located in Zone II. The treatments consisted of a factorial combination of four NPK rates (unfertilized control, 50N-11P-41.5K, 100N-22P-83K, and 150N-33P-124.5K kg/ha) with four rates of chicken manure (0, 1.4, 2.8, and 4.2 t/ha). The treatments were laid out in a randomized complete block design with three replications. Cassava height, stem girth, canopy diameter, leaf area index, and chlorophyll index were monitored over time and roots were harvested at 12 months after planting (MAP). Growth parameters and yield varied significantly (p < 0.01) both with NPK, manure application, and their interaction effects at 12 MAP. The combined application of 4.2 t/ha of chicken manure and 100N-22P-83 K kg/ha of mineral fertilizer resulted in the highest yields of 35.2 t/ha at Kabangwe. But, the highest average yield of 34.4 t/ha was recorded with the application of 2.8 t/ha manure and 100N-22P-83 K kg/ha mineral fertilizer at Mansa. This increased treatment yield by 24 and 29% over the sole NPK fertilizer application at Mansa and Kabangwe sites, respectively. Harvest index (HI) was higher when 2.8 t/ha chicken manure was applied in combination with 50N-11P-41.5K kg/ha at Kabangwe. But, the highest HI at Mansa site was achieved with the combination of 2.8 t/ha manure and 100N-22P-83 K kg/ha. This combination also resulted in the highest agronomic efficiency of N, P and K at both sites. It is concluded that cassava productivity and nutrient use efficiency can be improved through the integrated use of NPK and manure in Zambia.